Methods of deriving EULAR/ACR recommendations on reporting disease activity in clinical trials of patients with rheumatoid arthritis. Issue 10 (12th September 2008) - Karonitsch, T; Aletaha, D; Boers, M; Bombardieri, S; Combe, B; Dougados, M; Emery, P; Felson, D; Gomez-Reino, J; Keystone, E; Kvien, T K; Martin-Mola, E; et al.
Abstract : Objective: To use an evidence-based and consensus-based approach to elaborate recommendations on how to report disease activity in clinical trials of patients with rheumatoid arthritis (RA) endorsed by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR). Methods: After an initial expert meeting, during which relevant research questions were identified, a systematic literature search was performed using Medline, Embase and the Cochrane Library as sources. To ensure literature retrieved was comprehensive, we emphasised search algorithms that were sensitive rather than specific. The results of the literature search were discussed by the expert panel, modified and expanded, and were used as the basis for the elaboration of the recommendation in the consensus process. Finally, an independent ACR panel approved these items with some minor modifications. Results: The following pieces of evidence were obtained from the literature search: (1) timing and the sustaining of a response is relevant to achieve better outcomes; (2) composite disease activity indices have been used to define low disease activity and remission and these definitions have been validated as has the American Rheumatism Association (ARA) remission criteria. The "patient-reported symptom state" (PASS) is not yet well validated; (3) evidence was obtained to identify those measures, scales and patient-reported instruments, for which there is a documented association with relevant outcomes; (4) baseline disease activity is associated with disease activity levels at the end of follow-up; and (5) there was not sufficient evidence relating the added benefit of MRI or ultrasound over clinical assessments. Most data stemmed from observational studies rather than clinical trials and literature review was supplemented by input from experts. The results served as the basis for the elaboration of the seven recommendations by the experts. Conclusions: The approach based on scientific evidence from the literature as well as on expert input provided sufficient information to derive recommendations on reporting disease activity in RA clinical trials. The methodology, results and conclusions of this project were endorsed by EULAR and the ACR.